Predicting Aberrant Behaviors in Opioid-Treated Patients: Preliminary Validation of the Opioid Risk Tool - Webster, Lynn R.; Webster, Rebecca M. (Pain medicine (Malden, Mass.), 2005)
ABSTRACT Objective.  To provide clinicians with a brief screening tool to predict accurately which individuals may develop aberrant behaviors when prescribed opioids for chronic pain. Design.  One hundred and eighty‐five consecutive new patients treated in one pain clinic took the self‐administered Opioid Risk Tool (ORT). The ORT measured the following risk factors associated in scientific literature with substance abuse: personal and family history of substance abuse; age; history of preadolescent sexual abuse; and certain psychological diseases. Patients received scores of 0–3 (low risk), 4–7 (moderate risk), or ≥ 8 (high risk), indicating the probability of their displaying opioid‐related aberrant behaviors. All patients were monitored for aberrant behaviors for 12 months after their initial visits. Results.  For those patients with a risk category of low, 17 out of 18 (94.4%) did not display an aberrant behavior. For those patients with a risk category of high, 40 out of 44 (90.9%) did display an aberrant behavior. The authors used the c statistic to validate the ORT, because it simultaneously assesses sensitivity and specificity. The ORT displayed excellent discrimination for both the male (c = 0.82) and the female (c = 0.85) prognostic models. Conclusion.  In a preliminary study, among patients prescribed opioids for chronic pain, the ORT exhibited a high degree of sensitivity and specificity for determining which individuals are at risk for opioid‐related, aberrant behaviors. Further studies in a variety of pain and nonpain settings are needed to determine the ORT's universal applicability.